Monetary policy uncertainty and the market reaction to macroeconomic news - Kurov, Alexander; Stan, Raluca (Journal of Banking & Finance, 2018)
We examine whether monetary policy uncertainty influences the reaction of the equity, Treasury security, foreign exchange and crude oil markets, as well as medium-term interest rates, to U.S. macroeconomic announcements. Using intraday futures data, we show that in the presence of higher policy uncertainty the response to macroeconomic news weakens in the stock and crude oil markets and strengthens in the Treasury, interest rate and foreign exchange markets. In times of elevated monetary policy uncertainty, macroeconomic announcements impact the financial and crude oil markets to a large extent through expectations of future monetary policy.